Impaired central tolerance induces changes in the gut microbiota that exacerbate autoimmune hepatitis. Issue 128 (April 2022) - Centa, Monica; Weinstein, Erica G.; Clemente, Jose C.; Faith, Jeremiah J.; Fiel, M. Isabel; Lyallpuri, Robby; Herbin, Olivier; Alexandropoulos, Konstantina
Abstract: Medullary thymic epithelial cells (mTECs) induce T cell tolerance in the thymus through the elimination of self-reactive thymocytes. Commensal bacteria are also critical for shaping T cell responses in the gut and distal organs. We previously showed that mice depleted of mTECs (Traf6ΔTEC) generated autoreactive T cells and developed autoimmune hepatitis (AIH). In this report, we found that Toll-like receptor (TLR)-mediated microbial sensing on liver hematopoietic cells and the gut microbiota contributed to AIH development in Traf6ΔTEC mice. While adoptive transfer of thymic Traf6ΔTEC T cells in immune-deficient mice was sufficient for AIH development, colonization of germ-free mice with Traf6ΔTEC microbiota failed to induce AIH, suggesting that the gut microbiota contributes to but is not sufficient for AIH development. Microbiota-mediated exacerbation of AIH associated with increased numbers of hepatic Foxp3 + T cells and their increase was proportional to the degree of inflammation. The contribution of the gut microbiota to AIH development associated with an altered microbial signature whose composition was influenced by the qualitative nature of the thymic T cell compartment. These results suggest that aberrant selection of T cells in the thymus can induce changes in the gut microbiota that lead to exacerbation of organ-specific autoimmunity and AIH. Our results add to our understanding of the mechanisms of AIH development and create a platform towards developing novel therapeutic approaches for treating this disease. Highlights: The thymus-gut-liver axis regulates development of murine autoimmune hepatitis (AIH). Aberrant thymic T cell selection induces AIH and alters the gut microbiota. Hepatic microbial sensing and the gut microbiota exacerbate AIH. Microbiota-mediated hepatic Foxp3 + T cell production associates with AIH severity.